On the behaviour of tailings dams : Management in cold regions - Knutsson, Roger (Luleå tekniska universitet, Geoteknologi, 2018)
Associated to mining activities there is mine waste generated. The residues left over from mineralextraction processes are referred to as tailings, normally stored in surface tailings facilities. Thefacilities are usually confined by embankment dams, so called tailings dams. Sufficient stability of thetailings dams is essential, and a proper management of the tailings is needed in order to maintain asafe storage. However, optimal strategies for tailings management are very much site specific, andthere is no universal answer on how tailings management should be applied. Despite the availableguidelines, recommendations and current trends in the industry on how to handle tailings, theremust be a pertinent approach to optimize tailings management to the site-specific conditions. The aim with the work presented in this thesis is to enhance current practice in tailings managementin cold regions. Three sets of research objectives are presented, from which recommendations will begiven on how management can be adjusted for site-specific conditions. Firstly, depositional aspects in cold climate are studied. A methodology is proposed where thethermal regime is studied in a tailings facility with active deposition, i.e. raised tailings surface, andconcurrent freezing and thawing. Despite the fact that there is no natural permafrost in Sweden, thedeposition can imply generation of “man-made” permafrost in the facilities. The model is simple andeasily accessible data are used as input. With a proposed methodology, deposition schedules can bemodelled, and the deposition scheme can be adjusted in order to prevent permafrost generation intailings facilities. In addition to the depositional aspects in cold climate, a study is presented focusing on thaw stabilityof tailings beach slopes. The tailings beach is the inclined surface of settled tailings without pondedwater. For conventional tailings deposition, the beach slopes are relatively flat and the need for thawstability analyses is trivial. However, there is a current trend of ...